Acute effects of triathlon race on oxidative stress biomarkers - Mrakic-Sposta, S.; Gussoni, M.; Vezzoli, A.; Dellanoce,C.; Comassi, M.; Giardini, G.; Bruno, R. M.; Montorsi, M.; Corciu, A.; Greco, F.; Pratali, L. (Oxidative Medicine and Cellular Longevity, 2020)
The response to strenuous exercise was investigated by reactive oxygen species (ROS) production, oxidative damage, thiol redox status, and inflammation assessments in 32 enrolled triathlon athletes (41:9±7:9yrs) during Ironman® (IR), or half Ironman® (HIR) competition. In biological samples, inflammatory cytokines, aminothiols (glutathione (GSH), homocysteine (Hcy), cysteine (Cys), and cysteinylglycine (CysGly)), creatinine and neopterin, oxidative stress (OxS) biomarkers (protein carbonyl (PC), thiobarbituric acid-reactive substances (TBARS)), and ROS were assessed. Thirteen HIR and fourteen IR athletes ?nished the race. Postrace, ROS (HIR +20%; IR +28%; p<0:0001), TBARS (HIR +57%; IR +101%), PC (HIR +101%; IR +130%) and urinary neopterin (HIR +19%, IR +27%) significantly (range p<0:05-0.0001) increased. Moreover, HIR showed an increase in total Cys +28%, while IR showed total aminothiols, Cys, Hcy, CysGly, and GSH increase by +48, +30, +58, and +158%, respectively (range p<0:05-0.0001). ROS production was significantly correlated with TBARS and PC (R2=0:38 and R2=0:40; p<0:0001) and aminothiols levels (range R2=0:17-0.47; range p<0:01-0.0001). In particular, ROS was directly correlated with the athletes`age (R2=0:19;p<0:05), with ultraendurance years of training (R2=0:18;p<0:05) and the days/week training activity (R2=0:1 6;p<0:05). Finally, the days/week training activity (hours/in the last 2 weeks) was found inversely correlated with the IL-6 postrace (R2=-0:21;p<0:01). A strenuous performance, the Ironman® distance triathlon competition, alters the oxidant/antioxidant balance through a great OxS response that is directly correlated to the inflammatory parameters; furthermore, the obtained data suggest that an appropriate training time has to be selected in order to achieve the lowest ROS production and IL-6 concentration at the same time